The Cost of Adjustment to Green Growth Policies : Lessons from Trade Adjustment Costs - Porto, Guido (World Bank, Washington, DC, 2013)
Green growth policies confront firms and workers with adjustments that may create welfare costs for different segments of the population and cause reductions in near-term actual versus potential gross domestic product. There is little evidence on the cost of adjustment to climate change measures, and only limited evidence for more general environmental policies, especially in developing countries. Therefore, this paper canvasses the research on adjustment costs to trade policies to draw analogies and highlight differences compared with the potential impacts of green growth policies. Trade policies affect prices and work directly on technology choice. In the presence of adjustment costs, firms may experience impacts on wages, employment, and incentives to adopt alternative technologies. Both types of trade policy impacts may be amplified by technology availability and credit constraints. Many green growth policies are likely to work via the same mechanisms, that is, taxes on emissions or changes in technology requirements. However, trade liberalization is typically seen as offering higher total incomes, albeit with winners and losers. Green growth policies are thought of as welfare-enhancing at the collective level but may not be income-enhancing at the individual level. This implies much more difficulty in measuring the potential gains associated with green growth policies.